2002
DOI: 10.1080/13550280260422730
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus DNA load in cerebrospinal fluid and plasma of patients with AIDS-related lymphoma

Abstract: Detection of Epstein-Barr virus (EBV) DNA in the cerebrospinal fluid (CSF) is associated with acquired immunodeficiency syndrome (AIDS)-related brain lymphoma. Real-time polymerase chain reaction (PCR) was performed to quantify EBV DNA in CSF and plasma from 42 patients with AIDS-related non-Hodgkin's lymphoma (NHL). Twenty patients had primary central nervous system lymphoma (PCNSL) and 22 systemic NHL, including 12 with central nervous system involvement (CNS-NHL). As controls, 16 HIV-infected patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 20 publications
4
46
2
1
Order By: Relevance
“…The high EBV viral load in CSF (5.22 log copies/ml for the LightCycler EBV quantification kit and 4.67 log copies/ml for the RealArt EBV LC PCR kit) are in agreement with values previously reported (2,24). The LightCycler EBV quantification kit showed higher but wider distribution of viral load values than the RealArt EBV LC PCR kit.…”
Section: Discussionsupporting
confidence: 80%
“…The high EBV viral load in CSF (5.22 log copies/ml for the LightCycler EBV quantification kit and 4.67 log copies/ml for the RealArt EBV LC PCR kit) are in agreement with values previously reported (2,24). The LightCycler EBV quantification kit showed higher but wider distribution of viral load values than the RealArt EBV LC PCR kit.…”
Section: Discussionsupporting
confidence: 80%
“…These results were in agreement with some previously studies which also found 30% EBV positive in their NHL cases [22], [26]. On other hand, different studies reported higher association of the EBV with NHL as high as 80% in other developing countries [27], [10].…”
Section: Resultssupporting
confidence: 83%
“…Using quantitative techniques, high CSF EBV DNA levels have been found in these settings, and viral load may be clinically useful, with high plasma EBV DNA levels also potentially predictive of CNS involvement (26,106,155). The availability of EBV PCR, in conjunction with JCV PCR (see "JCV" section above) in AIDS patients presenting with an intracranial mass has been a major advance in the management of these patients.…”
Section: Ii) Immunocompromised Hosts Ebv Infection Is Associated Witmentioning
confidence: 99%
“…In a recent study, real-time PCR was performed to quantify EBV DNA in CSF and plasma from 42 patients with AIDSrelated NHL, with and without CNS involvement, as well as 20 patients with PCNSL and 16 HIV-infected controls with other CNS disorders (11,26). EBV DNA was detected in the CSF from 8 of 12 (67%) patients with CNS-NHL and 16 of 20 VOL.…”
Section: Ii) Immunocompromised Hosts Ebv Infection Is Associated Witmentioning
confidence: 99%